Does anti-IgE therapy prevent chronic allergic asthma-related bone deterioration in asthmatic mice?. (August 2022) - Gürgül, Serkan; Keskin, Özlem; Demirel, Can; Yaşar Özkars, Mehmet; Nural, Yahya
Abstract: Current evidence on the association between allergic diseases and bone metabolism indicates asthma may be a potential risk factor for bone health. Using anti-IgE has been proven effective in allergic asthma treatment with a good safety profile; however, its effects on bone health are unknown. Thus, we aimed to investigate whether: (i) chronic allergic asthma (CAA) causes any meaningful changes in bone, and if any, (ii) anti-IgE therapy prevents any CAA-induced adverse alteration. A murine model was used to study CAA. Thirty-two BALB/c male-mice were assigned into four groups (eight-mice/group): Control, CAA (treated with saline), CAA + 100 µg of anti-IgE (CAA + 100AIgE), and CAA + 200 µg of anti-IgE (CAA + 200AIgE) groups. After immunization, saline or anti-IgE was performed intraperitoneally for 8-weeks (in five-sessions at 15-days interval). Three-point bending test was used for the mechanical analysis. Bone calcium (Ca 2+ ) and phosphorus (P 3− ) as well as Ca/P ratio were evaluated using inductively-coupled plasma-mass-spectrometer (ICP-MS). Compared to control, reductions observed in yield and ultimate moments, rigidity, energy-to-failure, yield and ultimate stresses, elastic modulus, toughness, and post-yield toughness parameters of the CAA group were found significant ( P < 0.05). Similar declines were also detected regarding bone Ca 2+, P 3− and Ca/P ratio ( P < 0.05). Compared to control, we observed that 200 µg administration of anti-IgE in CAA + 200AIgE group hindered CAA-related impairments in mineral and mechanical characteristics of bone, while 100 µg in CAA + 100AIgE failed to do so. Our results showed CAA may cause bone loss, leading to a decrease in bone strength, and anti-IgE administration may dose-dependently inhibit these impairments in bone.